Pendampingan Refleksi Lokakarya PBD dan Disiplin Positif di SMP Kabupaten Banyuwangi - Sudiarti, Diah; Bukhori, Imam; Nurjanah, Umi; Pamungkas, Teguh Karya (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
The vision of Indonesia education is to create an advanced Indonesia that is sovereign, independent and has personality through the creation of Pancasila Student. The Driving School Program (PSP) aims to encourage the educational transformation process to increase student learning outcome holistically to realize the Pancasila Student Profile. At the school level, human resource competency is increased through training and mentoring. Accompanying the Data Based Planning (DBP) workshop reflection and positive discipline aims to analyze all workshop activities so that improvements can be made. The reflection was carried out online via Google Meet on January 27 2024. The reflection was attended by 22 participants, namely 4 Supervisor, 6 Principals and 12 PKPs. The result of this activity was the implementation of Positive Discipline instruction by SMP Negeri 1 Kabat, SMP Lazuardi Tursina and SMP Negeri 2 Srono. Internal monitoring has been implemented by all participating school, namely 6 schools. The application of positive discipline is carried out by creating class beliefs that can help students increase self-awareness and motivate students to develop their potential optimally. Positive discipline is also implemented without punishment and rewards. In conclusion, all schools show efforts and commitment to implementing positive discipline and carrying out various activities aimed at improving the quality of education and creating a conducive learning environment.